EFL Students’ Perception on the Use of YouTube Videos to Encourage Their Speaking Skill - Kurnia Budiyanti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
YouTube is effective as learning media nowadays. Therefore, many people all over the world use it in order to learn a new language including English. YouTube videos might encourage students’ speaking skill. There are a few researches conducted on EFL students’ perception in Islamic university of using YouTube videos to enhance their English speaking skills. The study aims to investigate students’ perception on the use of YouTube videos to encourage their English speaking skill. There were 30 of fourth semester of Arabic department students recruited in the study. To collect the data, the researcher used questionnaire and interview. The questionnaire was analyzed by using 5-Likert scale, while the short interview was used to find out the facts of the study. The findings reveal that the students have positive perception toward the use of YouTube videos in EFL classroom. It was found out that YouTube videos help them a lot to do their speaking assignment because they have a real model from native speaker. Hence, it is concluded that YouTube videos are really worthy to enhance the students’ speaking skill. Keywords: EFL students’ perception; YouTube videos; speaking skill; learning media